Kebijakan Penerbangan Perintis di Indonesia: Latar Belakang, Tantangan dan Kontribusi - Tangkilisan, Yuda Benharry (UI Scholars Hub, 2011)
It is a study of the Indonesian airline policy and the need of developing market for air traffic. Theresearch is taken through the written policies of the heads of state and the ministers of communicationfrom 1950 to the reformation era, and the interinsular flight schedules that were developed throughoutthe time. The primary objective of an understanding of an archipelagic conception of air communicationhas become the major concern of the independent republic of Indonesia since its independence in1945.It was to maintain a strategic consideration for national purpose. The result of which, the effort ofthe transfer of the colonial airline system, the KLM, to the Indonesian national airline, the GIA, wassuccessfully achieved. As the national air traffic was subsidized by thegovernment, the commercial linewas partly subsidized for a national security reason to control the air traffic. Therefore, the Indonesianair transportation is to bridge the need for integrating the archipelago for effort of ethnic integration and for a national unity in a wide-spread region, despite the need for profit. However, some commercialendeavors have been initiated in the post-Soeharto era, which resulted a breakdown ofcertain airlinecompanies. Facing the globalization, the policy would accommodate the air traffic businesses to developtheir facilities for fulfilling the demand of regional welfare, but yet to increasing the supervision of thenational policy on archipelagic stability.